Revisiting Why Plants Become N Deficient Under Elevated CO2: Importance to Meet N Demand Regardless of the Fed-Form - Igarashi, Maaya; Yi, Yan; Yano, Katsuya (Frontiers in Plant Science, 2021)
Increases in plant biomass under elevated CO2 (eCO2) are usually lower than expected, and N-deficiency induced by eCO2 is often assumed to be responsible. Several hypotheses explain the induced N-deficiency: 1) eCO2 inhibits nitrate assimilation, 2) eCO2 lowers nitrate acquisition with reduced transpiration, or 3) eCO2 reduces plant N concentration with increased biomass. We tested them using C3 (wheat, rice, and potato) and C4 plants (guinea grass, and Amaranthus) grown in chambers at 400 (ambient CO2, aCO2) or 800 (eCO2) µl l-1 CO2. In most species, we could not confirm hypothesis 1) by measurements of plant nitrate accumulation and δ15N value of organic-N. The exception was rice showing a slightly inhibited nitrate assimilation at eCO2, but the biomass was similar between the nitrate- and urea-fed plants. Contrary to hypothesis 2), eCO2 did not decrease plant nitrate acquisition despite reduced transpiration because of enhanced nitrate acquisition per unit transpiration in any species. Comparing to aCO2, eCO2 remarkably enhanced water-use efficiency, especially in C3 plants, decreasing water demand for CO2 acquisition. Since our results supported hypothesis 3) without any exception, we then examined if lowered N concentration at eCO2 indeed limits the growth by using C3 wheat and C4 guinea grass under various levels of nitrate-N supply. While eCO2 significantly increased relative growth rate (RGR) in wheat but not guinea grass, each species increased RGR with higher the N supply and then reached a maximum as no longer N limited. To achieve the maximum RGR, wheat required a 1.3-fold N supply at eCO2 than aCO2 with 2.2-fold biomass; however, the N requirement by guinea grass was less affected by the CO2 condition. The results reveal that accelerated RGR by eCO2 could create the demand for more N, especially in leaf sheath rather than leaf blade in wheat, causing N-limitation unless the additional N was supplied. We concluded that doubled CO2 strengthens N-limitation with an accelerated growth rate rather than inhibited nitrate assimilation or acquisition. Our results suggest that plant growth under higher CO2 will become more dependent on N but less dependent on water to acquire both CO2 and N.